2017
DOI: 10.1021/acs.jctc.7b00001
|View full text |Cite
|
Sign up to set email alerts
|

Critical Comparison of Biomembrane Force Fields: Protein–Lipid Interactions at the Membrane Interface

Abstract: Molecular dynamics (MD) simulations offer the possibility to study biological processes at high spatial and temporal resolution often not reachable by experiments. Corresponding biomolecular force field parameters have been developed for a wide variety of molecules ranging from inorganic ligands and small organic molecules over proteins and lipids to nucleic acids. Force fields have typically been parametrized and validated on thermodynamic observables and structural characteristics of individual compounds, e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 80 publications
3
83
1
Order By: Relevance
“…Large number of benchmark studies have been already performed to compare force fields for proteins and lipids. [45][46][47][48][49][50][51][52][53][54] In most cases, discrepancies could be observed between the simulations and the experimental data.…”
Section: Introductionmentioning
confidence: 94%
“…Large number of benchmark studies have been already performed to compare force fields for proteins and lipids. [45][46][47][48][49][50][51][52][53][54] In most cases, discrepancies could be observed between the simulations and the experimental data.…”
Section: Introductionmentioning
confidence: 94%
“…Sampling of the configurational space of CYP-membrane systems is challenging and, for this purpose, we have chosen to combine running longer CG replicas, for which convergence can be more readily monitored both within and between replicas, with shorter AA replicas starting from representative coordinates generated in CG simulations. Encouragingly, a recent critical comparison of force fields for simulating diverse proteinmembrane systems showed rather good performance for protein-lipid interactions at the membrane interface for the atomic detail AMBER ff14sb/LIPID 14 force field combination that we have used in this work (52). Moreover, the similarity of the CYP-membrane arrangements from our CG and AA simulations as well as the agreement with experimental observations suggests that our simulations can be used to examine the dependence of CYP positioning in the membrane on protein sequence.…”
Section: Discussionmentioning
confidence: 84%
“…In principle, full-peptide insertion values could be obtained via potential of mean force (PMF) partitioning calculations, as previously shown for both atomistic [16, 17] and coarse grained representations [18, 19]. However, we and others have shown that such simulations involve enormous convergence challenges [20, 21], which are related to the strong bilayer perturbation caused by the transition between surface and transmembrane state.…”
Section: Introductionmentioning
confidence: 99%